Genetic association of interleukin‐2, interleukin‐4, interleukin‐6, transforming growth factor‐β, tumour necrosis factor‐α and blood concentrations of calcineurin inhibitors in Turkish renal transplant patients. (26th March 2015) - Seyhun, Y.; Ciftci, H. S.; Kekik, C.; Karadeniz, M. S.; Tefik, T.; Nane, I.; Turkmen, A.; Oguz, F. S.; Aydin, F.
Summary Cytokines are essential for the control of the immune response as most of the immunosuppressive drugs target cytokine production or their action. The calcineurin inhibitors (CNIs) cyclosporine (CsA) and tacrolimus are immunosuppressive drugs widely used after renal transplantation to prevent allograft rejection. They are characterized by large interindividual variability in their pharmacokinetics; therefore, monitoring their blood concentrations is important to predict their optimal dosage following transplantation. Calcineurin inhibitors inhibit the phosphatase activity of calcineurin, thereby suppressing the production of other cytokines such as transforming growth factor (TGF‐β), tumour necrosis factor‐α (TNF‐α), interleukin (IL)‐6, IL‐2, and IL‐4. The aim of this study was to investigate the relationship between polymorphisms of cytokines and blood concentrations of CNIs in renal transplant patients. The study included 53 CsA‐treated renal transplant patients and 37 tacrolimus‐treated renal transplant patients. Cytokine polymorphisms were analysed using polymerase chain reaction (PCR) sequence‐specific primers with the cytokine CTS‐PCR‐sequence‐specific primers Tray Kit; University of Heidelberg. Blood concentrations of CNIs were determined with Cloned Enzyme Donor Immunoassay (CEDIA) method. Patients with TC genotype of TGF‐β at codon 10 had lower CsA blood concentrations than the TT and CC genotypes (P = 0.005) at 1 month in CsA treatment group. The ratio of blood concentration/dose of CsA for patients with TGF‐β1‐codon 10 TC genotype was lower than for patients with TT, CC genotypes, and the dose given to these patients was higher in the first month (P = 0.046). The ratio of blood concentration/dose of CsA for patients with IL‐2‐330 GG genotype was higher than for patients with GT, TT genotypes, and the dose given to these patients was lower at first month and sixth months (P = 0.043, P = 0.035 respectively). The tacrolimus blood concentrations were significantly higher in patients with the genotype GG of IL‐2‐330 (P = 0.012) at the third month. Patients who had the TC genotype TGF‐β codon 10 had lower CsA blood concentrations and this group had higher acute rejection (P = 0.033). These results suggest that the genotyping for TGF‐β‐codon 10, IL‐2‐330 and IL‐6‐174 polymorphisms may help individualized immunosuppressive dosage regiments.